Educational Assessment and Inclusive Education Paradoxes, Perspectives and Potentialities - Ydesen, Christian; Milner, Alison L.; Aderet-German, Tali; Caride, Ezequiel Gomez; Ruan, Youjin (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
XXXIII, 357 p. 13 illus.